Using Exogenous Elasticities to Induce Factor Substitution in Input-Output Price Models - Truchon, Michel (The Review of Economics and Statistics, 1984)
A device is presented that allows the user of any input-output price model to induce modifications in some selected coefficients in response to changes in prices. These modifications are induced by specifying the values of some elasticities, whenever they are defined. These values may come from other studies, from the user's own knowledge or beliefs about the situation, or from those of experts. If subjective elasticities are used, a simple rationality rule greatly reduces the task of determining their values when the substitution between two inputs or two groups of inputs is assumed to be a function of their prices only. This assumption does not prevent there being, in a second stage, substitution between these two inputs treated as a group and other inputs or groups of inputs.